Antitumor Activity of Propolis on Differantiated Cancer Cell Lines - Nese Ersoz Gulcelik; Dilara Zeybek; Figen Kaymaz; Omur Gencay; Bekir Salih; Kadriye Sorkun; Aydan Usman; Esin Asan (Medicine Science, 2012)
Propolis is a natural bee product with several pharmacological activities. Nowadays, it is also investigated for its antitumor properties. There are contraversies on the antitumor activity of propolis, not all tumour cells seem to respond to propolis treatment. The aim of our study is to evaluate the activity of propolis on differantiated thyroid cancer cell lines. Tyripan blue test and MTT assay were performed to evaluate the cell viability of B-CPAP cells after propolis treatment and compared with propolis free cells and normal thyroid cells. Evaluation with light microscopy revealed after treatment with propolis, cell count decreased and B-CPAP cells displayed morphologic changes with a smaller appearance. Tyripan blue exclusion test showed a decrease in cell viability in different concentrations of propolis at 48 and 72 h. Cell viability was measured by MTT after the treatment of B-CPAP cells with propolis at 72 h. The decrease in cell viability was statistically significant only at 0.0001 diluted propolis (p=0.048). The decrease in cell viability in normal thyroid cell line was not statistically significant. In conclusion, propolis have weak antitumor activity on differantiated thyroid cell line which may contribute to different degrees of sensitivity of propolis among cancer cells. [Med-Science 2012; 1(4.000): 292-300]